Design and Preliminary Validation of Conversion Flight Scheme for a Retractable Morphing Aircraft - NIE Bowen; LIU Zhitao; ZENG Weiping; LIANG Yong; HAN Jianfei (Kongzhi Yu Xinxi Jishu)
It briefly introduced the overview and flight mechanics of a retractable morphing vertical take-off and landing (VTOL) unmanned aerial vehicle (UAV), and presented a flight control scheme for conversion corridor. Towards the beginning and ending section of conversion corridor, a quad-rotor and a fixed-wing aircraft was selected as the typical research benchmark for flight control scheme design and simulation, which aimed to research on the transformation between VTOL, high speed cruise mode and conversion flight mode before a prototype retractable aircraft would be developed. At last, the feasibility and effectiveness of the conversion flight scheme were tested and preliminarily validated via ground and flight tests in the wind tunnel.